2010
DOI: 10.1002/ejoc.201000978
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Aspects of Aromaticity: Interrelations between Intramolecular Hydrogen Bonds, Steric Effects and π‐Electron Delocalisation in Nitroanilines

Abstract: The influence of intramolecular hydrogen bonds and steric hindrance on distortion from planarity of the benzene ring and its aromaticity is shown for a series of substituted 2,4,6‐trinitroanilines. The crystal structure geometry and thegeometry optimized at the B3LYP/6‐311++G** level are compared with analogues without intramolecular hydrogen bonds. The HOMA index and the parameter ΔP describing the distortion from planarity of the benzene ring were used to characterize the aromacity of the investigated molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…To our knowledge, no systematic research on a relationship between distortion from planarity and decrease of aromaticity for a family of substituted [2.2]­paracyclophanes has been done yet. We compare the HOMA aromaticity index with the nonplanarity parameter Δ P for the experimental structures of [2.2]­paracyclophanes collected in the CSD databases …”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no systematic research on a relationship between distortion from planarity and decrease of aromaticity for a family of substituted [2.2]­paracyclophanes has been done yet. We compare the HOMA aromaticity index with the nonplanarity parameter Δ P for the experimental structures of [2.2]­paracyclophanes collected in the CSD databases …”
Section: Introductionmentioning
confidence: 99%
“…A significant decrease in aromaticity was found for several overcrowded 2,4,6-trinitroanilines (Majerz & Dziembowska, 2011.…”
Section: Introductionmentioning
confidence: 95%
“…This effect results from a through-resonance interaction and increasing participation of a quinoid resonance structure (Krygowski & Stę pień , 2005;Dobrowolski et al, 2009;Szatylowicz, Siodla et al, 2016). Very low to negative HOMA values were found for some overcrowded nitro-amino derivatives (Omelchenko et al, 2012;Majerz & Dziembowska, 2011. It was shown that the factors responsible for reduction down to anti-aromaticity were the formation of an intramolecular NHÁ Á ÁO hydrogen bond between the amino and nitro groups as well as considerable deviation from planarity of the aromatic ring caused by steric interaction between the bulky groups substituted onto the benzene ring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, as the bonds elongate and became weaker, the aromaticity of the rings also decreases, and this is the energetic contribution to de-aromatization. Majerz and Dziembowska [23], recently, have shown that intramolecular hydrogen bonds, steric effects and p-electron delocalization strongly influences the HOMA values. In this study, besides these effects, it will be shown that symmetry can also have a biased influence on the evaluation of aromaticity by this criterion and, to the best of our knowledge this has not yet been spotted in other studies.…”
Section: Introductionmentioning
confidence: 99%